BEHIND PLATO’S SHADOWS AND TODAY’S MEDIA MONSTERS - Pizzato, Mark (Homo Mimeticus II, 2024)
This chapter adds to mimetic studies by exploring Plato’s ancient cave allegory through psychology, anthropology, and neuroscience, regarding current screen media and repeated mass shootings in the United States. It considers developmental, ancestral, and "inner theater" sources of ego and group rivalry, involving animal-human emotional drives. Comparing Plato’s metaphors with prehistoric cave art and recent brain mapping discoveries, this spelunking expedition finds a dark side to rational idealism in predatory scapegoating, as homo mimeticus path or "patho(-)logy" of the " vita mimetica " (Lawtoo 2022).¹ The interplay between inner and outer theater networks reveals subconscious Trojan Horse influences and dangerous melodramatic ideals,